Government Communication in Improving Public Services in Cimaragas Village, Cimaragas District, Ciamis Regency - Wisnu Eko Yuniaryuda; Erlan Suwarlan; Aditiyawarman (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This research is motivated by the suboptimal government communication in improving public services in Cimaragas Village, Cimaragas District, Ciamis Regency. Problems that arise include the community not receiving information evenly and the services provided are less than optimal due to ineffective information delivery. The purpose of this study is to determine how government communication improves public services in Cimaragas Village. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through structured interviews and direct observation. This study uses Redding's organizational communication climate theory which includes five main dimensions, namely trust, supportiveness, openness in downward communication, participatory decision-making, and emphasis on high-performance goals. The results show that government communication in Cimaragas Village is not running optimally. This is caused by the community's low understanding and ability to grasp information from the village government, as well as the limited ability of the apparatus in using information technology. As a result, information cannot be disseminated quickly and evenly to the community. A more adaptive and participatory communication strategy is needed so that public services can run more effectively. Keywords: Government Communication, Public Services, Information